2020
DOI: 10.1371/journal.pone.0227604
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum beta-lactamase (ESBL)-producing and non-ESBL-producing Escherichia coli isolates causing bacteremia in the Netherlands (2014 – 2016) differ in clonal distribution, antimicrobial resistance gene and virulence gene content

Abstract: Background Knowledge on the molecular epidemiology of Escherichia coli causing E. coli bacteremia (ECB) in the Netherlands is mostly based on extended-spectrum beta-lactamase-producing E. coli (ESBL-Ec). We determined differences in clonality and resistance and virulence gene (VG) content between non-ESBL-producing E. coli (non-ESBL-Ec) and ESBL-Ec isolates from ECB episodes with different epidemiological characteristics. Methods A random selection of non-ESBL-Ec isolates as well as all available ESBL-Ec blood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…In our study, more than two-thirds of the isolates (63%) were ESBL-EC. A high prevalence of ESBL-EC strains have been raised quite consistently from previous studies carried out in Morocco (Lahlou Amine et al, 2009;Romli et al, 2011; El Bouamri et al, 2014a;El bouamri et al, 2014b;Sbiti et al, 2017) and outside (Gravey et al, 2017;Critchley et al, 2019;Koguchi et al, 2020;Tan et al, 2020;van Hout et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…In our study, more than two-thirds of the isolates (63%) were ESBL-EC. A high prevalence of ESBL-EC strains have been raised quite consistently from previous studies carried out in Morocco (Lahlou Amine et al, 2009;Romli et al, 2011; El Bouamri et al, 2014a;El bouamri et al, 2014b;Sbiti et al, 2017) and outside (Gravey et al, 2017;Critchley et al, 2019;Koguchi et al, 2020;Tan et al, 2020;van Hout et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…Though usually considered a human-specific lineage, ST73 is most probably an ubiquitous urinary pathogen, because it has recurrently been described in animals, both in diseased and healthy contexts (Wagner et al, 2014;Liu et al, 2015;Bourne et al, 2019). Also, ST73 may well be under-reported in the literature because most papers have focused on ESC-R genes, which are less frequently found in this ST than in other ones such as ST131 or ST38 (Hertz et al, 2016;Manges, 2016;Van Hout et al, 2020). The prevalence of ESC-R E. coli in this study was 5.3% (33/618), which is fairly low compared with what has recently been described in the United Kingdom (18.4%), Switzerland (32.1%) or even in France in 2011 (18.5%) (Zogg et al, 2018a;Bortolami et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study conducted in Dutch hospitals, between 2014 and 2016, the dominant clone found among ESBL- E. coli blood isolates was ST131 carrying bla CTX-M-15 . 19 Furthermore, in a study conducted in the Netherlands in 2016, the clone was isolated among community-associated and hospitalized patients, 20 indicating that the clone existed in both the community and hospitals in the Netherlands before the number of refugees started to increase in 2015 and 2016.…”
Section: Discussionmentioning
confidence: 99%